ARABIC MIGRATION LITERATURE: JUBRAN KHALIL JUBRAN AND MICHAEL NUAYMA IN THE CONTEXT OF CREATIVITY - Mustafayev, Z.T (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
One of the main features of the poetic work of Jubran Khalil Jubran was a description of human feelings. He tried to express the spiritual, philosophical, socio-political and moral nuances of love in all its subtleties. He emphasized that love, which is not updated daily, dies every day. Tolerance is arrogant love. Love each other, but do not turn love into chains. It is better to have a wide sea of love between the shores of your souls. Sing, dance and rejoice together, but each of you should be alone, like the strings of a lute, although they only make music. Love gives nothing but itself and takes nothing but itself. Therefore, love has nothing, but it cannot be obsessed because love is only love. Love, which seeks nothing but the desire to reveal its secrets, is not love, but a network that can only claim to be useless. Daily undivided love becomes a habit, which, in turn, turns into slavery. Love and doubt never meet.